Integrative network toxicology and molecular docking reveal 4-Nonylphenol’s multifaceted mechanisms in breast cancer pathogenesis - Congli Jia; Fu Yang (PLoS ONE, 2025)
Objective This study employs integrated network toxicology and molecular docking to investigate the molecular basis underlying 4-nonylphenol (4-NP)-mediated enhancement of breast cancer susceptibility. Methods We integrated data from multiple databases, including ChEMBL, STITCH, Swiss Target Prediction, GeneCards, OMIM and TTD. Core compound-disease-associated target genes were identified through Protein-Protein Interaction (PPI) network analysis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were subsequently employed to elucidate the potential molecular functions and biological pathways associated with these key targets. Molecular docking using AutoDock Vina was conducted to investigate the binding interactions between the core genes and 4-NP. Furthermore, the miRDB database was utilized to identify potential microRNAs (miRNAs) that may exert regulatory control over the pivotal genes. Results Five hub breast cancer target genes associated with 4-NP exposure were screened, containing TP53, HDAC1, ESR1, CTNNB1 and MYC. GO and KEGG analyses revealed that intersecting genes mainly influenced PI3K-Akt signaling, MicroRNAs in cancer, Chemical carcinogenesis−receptor activation and MAPK signaling. Molecular docking confirmed strong binding affinities of 4-NP to these hub genes. Subsequently several high-confidence candidate regulatory miRNAs especially miR-22, -148a, -181a and −152 were identified that shed light on miRNA regulatory mechanisms by which 4-NP increases breast cancer risk. Conclusion Our study demonstrates that 4-NP exposure perturbs protein conformational of hub targets, activating cascades and dysregulating signaling pathway to potentiate breast cancer risk. Furthermore, we identify a novel miRNA-mediated regulatory axis alongside MAPK signaling as critical mechanisms underpinning 4-NP toxicity.